2017
DOI: 10.1080/24694193.2017.1316789
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Young Service Users to Provide Feedback on their Experience: An Evaluation of the Pilot Implementation of Children and Young People Accessible Friends and Family Test in General and Dental Practices in NHS England South (South Central)

Abstract: Involvement of service users in the delivery and development of services by providing unique feedback on their own experiences is a well-established feature of continuing improvement and quality enhancement. The Friends and Family Test (FFT) is a tool that supports the fundamental principle that people who use NHS services should have the opportunity to provide feedback on their experience, however children and young people are a group of key stakeholders whose voice has not been routinely sought. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…From a review of 12 eligible studies, it was identified that there are mixed results regarding the usefulness of NPS data in healthcare. Our findings suggest that NPS has immediate benefits, such as being understood by a wide range of patients 19–21 and eliciting a large number of responses 14 . Furthermore, NPS could provide several indirect benefits, such as encouraging staff and patients to focus on the importance of patient experience and feedback, as well as encouraging the use of real‐time patient surveying.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…From a review of 12 eligible studies, it was identified that there are mixed results regarding the usefulness of NPS data in healthcare. Our findings suggest that NPS has immediate benefits, such as being understood by a wide range of patients 19–21 and eliciting a large number of responses 14 . Furthermore, NPS could provide several indirect benefits, such as encouraging staff and patients to focus on the importance of patient experience and feedback, as well as encouraging the use of real‐time patient surveying.…”
Section: Discussionmentioning
confidence: 86%
“…Two studies noted that the NPS question was well‐understood by a diverse range of patients, including those with low literacy 19,20 . However patients may also experience concerns about the recommendation question, particularly if they do not have a choice of healthcare provider 22 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations